Information Needs of Female Prisoners: A Study of Mobile Library Services at the Women Detention Center, Class IIB Bengkulu, Indonesia - Azzahra Fatimah; Samosir Fransiska Timoria; Siregar Rosi L Vini (Indonesian Journal of Librarianship, 2025)
Abstract   Background: Access to relevant information is an important aspect of the rehabilitation and social reintegration process for inmates. However, the specific information needs of female prisoners have not been fully identified, while the reading materials provided by the mobile library service remain limited and do not yet align with the preferences of female inmates. Purpose: This study aims to identify the information needs of female inmates at the Women's Detention Center Class IIB Bengkulu and to analyze the contribution of mobile library services in supporting the rehabilitation process. Method: This research employed a descriptive qualitative approach. Data were obtained through in-depth interviews and direct observations involving female inmates, correctional officers, and librarians in charge of the mobile library service. The data analysis followed an interactive process encompassing five stages: data collection, raw data description, data reduction, data categorization, and the construction of inter-category relationships. Result: Female inmates showed a high interest in affective information such as fiction novels and language arts books, but the available collection was inadequate. Social and personal integration information was available but underutilized due to a lack of understanding and interest. This indicates a gap between actual needs and the provision of information services.  Conclusion: The mobile library service plays a significant role in meeting the information needs of female inmates, but improvements are needed through collection diversification, increased procurement frequency, and the implementation of information literacy programs to make the service more relevant to their needs.